The Relationship of Knowledge, Parity and Anxiety With the Event of Severe Preeclamsia in Hospital General of Wood Area 2021 - Reni Aryanti; Siti Aisyah; Helni Anggraini (Science Midwifery, 2022)
Preeclampsia is a health problem that requires special attention because preeclampsia is a high cause of maternal and perinatal mortality, especially in developing countries. Until now preeclampsia and eclampsia are still "the disease of theories", because the incidence of preeclampsia-eclampsia remains high and results in high maternal morbidity and mortality. Many theories suggest that the cause of preeclampsia is placental ischemia. However, this theory cannot explain all the things related to the disease. Apparently not only one factor, but many factors that cause preeclampsia and eclampsia (multiple causation). Factors that are often found as risk factors include parity, knowledge and anxiety. This study aims to determine the relationship between knowledge, parity and anxiety with the incidence of severe preeclampsia at the Kayuagung Hospital in 2021. The design of this research is quantitative using an analytical survey method with a cross sectional approach. The population in this study were all pregnant women who were treated at the Kayuagung Hospital from January to December 20, 2021. The sample used was some pregnant women who were treated at the Kayuagung Hospital. Sampling technique Incidental Sampling / Accidental Sampling, amounting to 33 respondents. The statistical results of the chi-square test obtained p value = 0.015 <0.05, so it can be concluded that there is a relationship between knowledge and the incidence of severe preeclampsia, the statistical results of the chi-square test obtained p value = 0.033 <0.05, so it can be concluded it was concluded that there was a relationship between parity and the incidence of severe preeclampsia and the statistical results of the chi-square test obtained p value = 0.067 <0.05, so it could be concluded that there was no relationship between parity and the incidence of severe preeclampsia. It can be concluded that there is a relationship between knowledge and parity with the incidence of severe preeclampsia at the Kayuagung Hospital in 2021 and there is no relationship between simultaneous anxiety and the incidence of severe preeclampsia in the Kayuagung Hospital in 2021